2019
DOI: 10.1186/s40644-019-0270-0
|View full text |Cite
|
Sign up to set email alerts
|

CT-assessed sarcopenia is a predictive factor for both long-term and short-term outcomes in gastrointestinal oncology patients: a systematic review and meta-analysis

Abstract: BackgroundThe impact of sarcopenia on the outcome of gastrointestinal (GI) oncological patients is still controversial. We aim to discuss the prevalence of sarcopenia and its relation to the oncological outcome.MethodsEmbase, Medline, PubMed, and the Cochrane library were systematically searched for related keywords. Studies using CT to assess sarcopenia and evaluate its relationship with the outcome of GI oncological patients were included. Long-term outcomes, including overall survival and disease-free survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
99
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(107 citation statements)
references
References 102 publications
(148 reference statements)
7
99
0
1
Order By: Relevance
“…Our subgroup results found that when considering the reasons for admission, critically ill patients with sarcopenia have an increased risk of mortality, profoundly con rming that sarcopenia could be a prognostic factor in critical illness. Our ndings are in line with previous research, which has found that older adults with sarcopenia are at increased risk of mortality in other settings, such as the community 36 , nursing homes 43 , or in an oncology setting [44][45][46] . According to published studies, the main reason explaining the relationship between sarcopenia and mortality is lower muscle mass, which has been con rmed as a strong predictor for an increased risk of death 31,47 .…”
Section: Discussionsupporting
confidence: 92%
“…Our subgroup results found that when considering the reasons for admission, critically ill patients with sarcopenia have an increased risk of mortality, profoundly con rming that sarcopenia could be a prognostic factor in critical illness. Our ndings are in line with previous research, which has found that older adults with sarcopenia are at increased risk of mortality in other settings, such as the community 36 , nursing homes 43 , or in an oncology setting [44][45][46] . According to published studies, the main reason explaining the relationship between sarcopenia and mortality is lower muscle mass, which has been con rmed as a strong predictor for an increased risk of death 31,47 .…”
Section: Discussionsupporting
confidence: 92%
“…Diminished muscle mass and strength defining sarcopenia have been increasingly reported as important components of a network of elements influencing perioperative outcomes in cancer surgery. Diagnosis of sarcopenia, as reasonably expected, was associated with increased postoperative complications, length of hospital stay, and mortality in various clinical settings 2 …”
supporting
confidence: 64%
“…Then, we chose the newest meta‐analysis with the largest number of studies. Finally, 54 health‐related outcomes extracted from 30 meta‐analyses 10,22‐50 were reported in this umbrella review. These 54 outcomes were mainly about prognostic outcomes of tumor, postoperative outcomes, age‐related outcomes, metabolic outcomes, and other outcomes.…”
Section: Resultsmentioning
confidence: 99%